Measuring Strategic Business Value Of Digital Transformations In The Retail Industry - Kota, Deepak (Digital Repository of Theses - SSBM Geneva, 2024)
The Retail industry is going through a paradigm shift and the next generation of customers are leaning towards purpose-driven retail, demanding new levels of value like instant delivery, and seamless experiences at best prices. Retailers are enabling value creation with differentiated physical and digital shopping experiences driven by innovative business capabilities. CXOs are making significant investments in digital transformation initiatives adopting technologies like artificial intelligence, cloud, Internet of Things, and augmented reality. Chief Financial Officers (CFOs) are challenged in evaluating the business case and measuring success of these digital programs due to inadequate and inconsistent valuation practices. Existing academic research indicates that traditional return on investment (ROI) measurement frameworks are limited in their ability to deliver insights on true business value achieved through digital investments. Traditional measurement methods of transformation benefits like free cash flows or net present value involve long payback cycles and typically have intangible outcomes. The value impact of digital technology investments is a challenge at enterprise level and monitoring this performance extends beyond traditional methods to non-financial metrics aligned to the business objectives of the program. The proposed study would examine the value provided by digital transformations implemented in the global retail business. The study has a long-term goal of providing CFOs the required tools to measure transformation benefits through a unified digital ROI framework aligned to the retail business value chain. It assesses the business outcomes of these initiatives, including their impact on financial performance, cash flows, and the prospect of defining an all-encompassing business value framework. A research approach involving a digital survey was conducted to gather insights from practitioners of Digital technology transformations regarding their perspectives on methodology, approach, challenges, and recommendations for evaluating and optimizing ROI benefits. The outcome of this research was a structured benefits evaluation framework, Smart Gems, which is enriched by the fusion of real-world experiences and processional wisdom. Smart Gems enables business metric definition and effective measurement across the retail transformation value chain. CFOs should now be able to navigate confidently as they evaluate and approve complex digital initiatives and design effective governance practices for value management.